2021
DOI: 10.1029/2020sw002526
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Magnetic Perturbation Events Observed in Arctic Canada: 3. Occurrence and Amplitude as Functions of Magnetic Latitude, Local Time, and Magnetic Disturbance Indices

Abstract: We present 2 years of observations of ≥6 nT/s magnetic perturbation events (MPEs) from 5 high latitude Arctic stations. Most MPEs occurred within 30 min of a substorm onset, but substorms were neither necessary nor sufficient to cause MPEs. Premidnight and postmidnight MPEs had different temporal relations to substorms and occurred at slightly different latitudes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 50 publications
12
32
0
Order By: Relevance
“…A secondary peak of occurrence is observed in the dawn-noon sector. Some of these peaks below 70°N may be associated with MPEs since they are consistent with the 02-06 MLT distribution observed by Engebretson et al (2021) for the station at 65°N geomagnetic, as noted above. However, this is also a region in which Pc5 pulsations are the dominant wave activity (e.g.…”
Section: Accepted Articlesupporting
confidence: 86%
See 2 more Smart Citations
“…A secondary peak of occurrence is observed in the dawn-noon sector. Some of these peaks below 70°N may be associated with MPEs since they are consistent with the 02-06 MLT distribution observed by Engebretson et al (2021) for the station at 65°N geomagnetic, as noted above. However, this is also a region in which Pc5 pulsations are the dominant wave activity (e.g.…”
Section: Accepted Articlesupporting
confidence: 86%
“…MPEs are a broad class of large (hundreds of nT), localised, 5-10 min unipolar or bipolar pulses of 𝐵 ℎ which occur in the auroral zone during substorms, but are not necessarily associated with substorm onsets (Engebretson et al, 2019a(Engebretson et al, ,b, 2020(Engebretson et al, , 2021Belakhovsky et al, 2019;Dimmock et al, 2019;Apatenkov et al, 2020;Viljanen, 1997). They arise from transient phenomena in the magnetotail such as bursty bulk flows (BBFs) (Angelopoulos et al, 1992;Wei et al, 2021), dipolarising flux bundles (Liu et al, 2014), poleward-expanding discrete aurorae passing over the magnetometer site (Ngwira et al, 2018), and small-scale rapidly moving ionospheric current vortices (Apatenkov et al, 2020).…”
Section: Night-time Magnetic Perturbation Events (Mpe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers reporting results from this work were published in 2019 (Engebretson, Pilipenko, et al, 2019;Engebretson, Steinmetz, et al, 2019): the first paper presented statistical results using data from these magnetometers, and the second presented 3 case studies using auroral imagers and spacecraft data as well. A third paper (Engebretson et al, 2021, henceforth referred to as paper 3), as well as another study that compared MPEs observed in the Arctic and Antarctic using some of these stations as well as stations in Greenland (Engebretson et al, 2020), showed several differences in characteristics between premidnight and postmidnight MPEs. At least some of the postmidnight events were associated with auroral omega bands, as also noted by Viljanen et al (2001) and Apatenkov et al (2020).…”
mentioning
confidence: 99%
“…Therefore, significant efforts of the geophysical community are aimed at developing global MHD models of geomagnetic storm and substorm activity and incorporating the magnetotelluric response of the Earth to compute GICs (Pulkkinen et al., 2015; Zhang et al., 2012). However, beyond the largest space weather events, several studies suggest that there are more rapid, small‐scale and localized processes involved in generating some extreme GICs (Dimmock et al., 2020; Engebretson, Pilipenko, et al., 2019, Engebretson et al., 2021; Ngwira et al., 2015, 2018; Opgenoorth et al., 2020).…”
Section: Introductionmentioning
confidence: 99%